The effect of expectations and perceptions in service quality (An Empirical Study) - حمادي, سعد فرج (Journal of Economics and Administrative Sciences, 2016)
Abstract  The study aims to find out the impact of expectations and perceptions in determining the position of the customer service quality received by him. Represent the expectations and perceptions customer’s key of service quality determinants. The customer's requirements and needs main pivot, who must be built all events and activities and efforts of service organizations, including the hotel and organizations that operate in an environment known as highly competitive , intensification and  complexity of the conditions set by the customer and increasing day after day. The study sample of three Luxury hotels in Kurdistan region of Iraq a model. The use of service quality model and style factor analysis to obtain statistical results which showed that the expectations and perceptions customers of service quality dimensions (Tangibility, reliability, responsiveness, assurance, empathy) may have influenced the level of service quality received by customers surveyed hotels. While the results of the matrix factor analysis of the five criteria shown in customer expectations for service quality that the standard (responsiveness) was the first factor contribution rate (0.724), followed by tangibility, reliability and empathy standards and finally the standard (assurance) at the lowest contribution rate (0.024). The factor analysis of standards perceptions customers for services received showed that (reliability) was the first factor, followed by empathy, responsiveness and tangibility and the lowest percentage contribution to the standard (assurance) also.   Finally the service quality equation and a positive gap between expectations and perceptions customers in the dimensions of reliability, empathy and assurance. The quality while negative between expectations and perceptions customers appeared in dimensions (tangibility, responsiveness).